DIPLOMASI KOREA SELATAN MENDESAK JEPANG MENANDATANGANI AGREEMENT ON COMFORT WOMEN TAHUN 2011-2015 - Rizka Fauzia; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research analyze about steps of diplomacy by South Korea to urge Japan sign the Irreversible agreement called Agreement on comfort Woman on December 28,2015. The agreement consisting of statement deepest apology of Japan‟s goverment about their contribution to abduct almost 200 thousand women from some country specially from South Korea.Since world war I Japan‟s goverment abduct more than 200 thousand women from South Korea, Indonesia, and phillippines to be their sex slavery in order to comply their army‟s sex necessary and lack of abduct their citizen be their sex slavery. South Korea after world war II start to appear this issue and take the steps of diplomacy to urge Japan to have responsible about the issue .Japan refuse to take the responsible about what their goverment did in the past with some reason that abduct of more than 200 thousand women has done of person who want to take the profit from the war by abduct women and force them to be a sex slavery.But, after diplomacy by South Korea, Japan finally sign the irreversible agreement and take their responsible about this issue and the steps of diplomacy by South korea‟s Goverment will be explain in this research.Keywords : Diplomacy, South Korea, Japan, Jugun ianfu,Comfort Women,Agreement on comfort Women